On-chip electro-static discharge (ESD) protection for radio-frequency integrated circuits. ([2015]) - (Computer engineer), Cui, Qiang; Liou, Juin J; (Computer engineer), Hajjar, Jean-Jacques; (Computer engineer), Salcedo, Javier; (Computer engineer), Zhou, Yuanzhong; (Computer engineer), Srivatsan, Parthasarathy
No abstract available